I have some issues concerning the derivative of an absolute value $|x|$, the Heaviside function $\theta(x)$ and the Dirac Delta Distribution.

Given the definition of the Heaviside function \begin{equation} \theta(x) = \left\{ \begin{array}{ll} 1 \quad \text{for} \quad x \ge 0\\ 0 \quad \text{for} \quad x<0 \end{array} \right. \end{equation} I suppose it is right to express the first derivative of an absolute value as \begin{equation} \frac{d |x|}{dx} = \left\{ \begin{array}{ll} +1 \quad \text{for} \quad x > 0\\ -1 \quad \text{for} \quad x<0 \end{array} \right. \overset{!}{=} \theta(x) - \theta(-x), \end{equation} evaluating the derivatives of $|x|$ from the left and right side. Here I have some issues with the case of $x=0$ \begin{equation} \left.\frac{d |x|}{dx}\right|_{x=0}=\theta(0)-\theta(0)=1-1=0, \end{equation} which is not defined in my original "first derivative" of $d |x|/ dx$. So how can the first derivative of an absolute value be correctly expressed in terms of the Heaviside function?

Anyways taking my assumption of the first derivative for granted I want to perform a second derivative with the identity \begin{equation} \frac{d \theta(x)}{dx} = \delta(x) \end{equation}, which then leads to \begin{equation} \frac{ d^2 |x|}{dx^2} = \frac{d}{dx}(\theta(x)-\theta(-x)) = \delta(x)-\delta(-x)=\delta(x)-\delta(x)=0. \end{equation}

The last expression cannot be true and should be \begin{equation} \frac{d^2 |x|}{dx^2} = 2 \delta(x) \end{equation} following Second derivative of absolute value function proportional to Dirac delta function?

What am I missing to get to the correct expression?

  • $\begingroup$ $\frac{d|x|}{dx} = \text{sign}(x)$ because $|x| = \int_0^x \text{sign}(t)dt$. When integrating, the isolated value of $\text{sign}(x)$ at $x=0$ doesn't change anything. And $\frac{d\text{ sign}(x)}{dx}= 2 \delta(x)$ because $\text{sign}(x) = \int 2 \delta(x) dx$ $\endgroup$ – reuns May 13 '17 at 14:58

If you draw $|x|$ then you should see the derivative does depend on the direction you approach the point from. Trying to assign it a numerical value does not make sense. Your expressions are correct although you could try to assign the derivative to be infinite at $x=0$.

For your second point, the chain rule is missing from your calculation, $$ \frac{d\theta(-x)}{dx} = \left.\frac{d(-x)}{dx} \frac{d\theta(y)}{dy}\right\vert_{y=-x} = - \delta(y)\vert_{y=-x} = -\delta(-x)=-\delta(x) . $$

  • $\begingroup$ chain rule, got me again! $\endgroup$ – Knowledge May 13 '17 at 10:23

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.